Protocol for use of antibiotic prophylactic therapy in dental conducts, a literature review (Research, Society and Development, 2024)
The use of antibiotics prophylactically to perform dental procedures that can cause infection, called antibiotic prophylaxis. Aiming at this objective, the previous administration of antibiotics is based on doses of high concentration in the tissues at the time of conducts that may cause an infection in the so-called susceptible patients. The main goal is the prevention of bacterial endocarditis. The literature is unanimous in stating that these patients have valve prostheses, previous bacterial endocarditis, cyanotic congenital heart disease, valvular dysfunction, mitral valve prolapse, hypertrophic cardiomyopathy, rheumatic fever with valvular dysfunction, transplant recipients, and recent orthopedic prostheses (one year). The goal of this literature revisionis to consciousness the dental class for a proper pratice of prophilatic antibiotic therapy.